Kansas City vs. Oakland : the bitter sports rivalry that defined an era - Ehrlich, Matthew C., 1962- (Sport and society., 2019)
A driving ambition linked Oakland and Kansas City in the 1960s. Each city sought the national attention and civic glory that came with being home to professional sports teams. Their successful campaigns to lure pro franchises ignited mutual rivalries in football and baseball that thrilled hometown fans. But even Super Bowl victories and World Series triumphs proved to be no defense against urban problems in the tumultuous 1960s and 1970s. Matthew C. Ehrlich tells the fascinating history of these iconic sports towns. From early American Football League battles to Oakland's deft poaching of baseball's Kansas City Athletics, the cities emerged as fierce opponents from Day One. Ehrlich weaves a saga of athletic stars and folk heroes like Len Dawson, Al Davis, George Brett, and Reggie Jackson, and breaks down who won and who lost when big-time sports came to town.